Approximation of Modified Baskakov Operators Based on Parameter s - Mohammad, Ali J.; S. A. Abdul-Hammed,; T. A. Abdul-Qader, (Iraqi Journal of Science, 2021)
In this article, we define and study a family of modified Baskakov type operators based on a parameter . This family is a generalization of the classical Baskakov sequence. First, we prove that it converges to the function being approximated. Then, we find a Voronovsky-type formula and obtain that the order of approximation of this family is . This order is better than the order of the classical Baskakov sequence whenever . Finally, we apply our sequence to approximate two test functions and analyze the numerical results obtained.